2007
DOI: 10.1523/jneurosci.1877-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Cu/Zn-Superoxide Dismutase Associated with Amyotrophic Lateral Sclerosis Destabilizes Vascular Endothelial Growth Factor mRNA and Downregulates Its Expression

Abstract: Vascular endothelial growth factor (VEGF) plays a neuroprotective role in mice harboring mutations of copper-zinc superoxide dismutase 1 (SOD1) in familial amyotrophic lateral sclerosis (ALS). Conversely, the loss of VEGF expression through genetic depletion can give rise to a phenotype resembling ALS independent of SOD1 mutations. Here, we observe a profound downregulation of VEGF mRNA expression in spinal cords of G93A SOD1 mice that occurred early in the course of the disease. Using an in vitro culture mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 75 publications
(89 reference statements)
8
78
1
1
Order By: Relevance
“…38,[41][42][43] Of these neurotrophic factors, VEGF is well known to have an important function in the pathogenesis of ALS. [31][32][33][34]37,38 The genetically modified human NSCs we established, F3.VEGF cells, were confirmed to release four times of VEGF165, the most abundant and biologically active isoform in vivo, compared with the parental F3 cells as we have reported previously in animal models of stroke. 28 Ex vivo gene therapy by genetically modified cells to carry growth factor gene has no risk related with virus injection during the in vivo gene therapy, and the transplanted cells can deliver growth factor over a large area as the cells migrate and are integrated to the host brain tissue.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…38,[41][42][43] Of these neurotrophic factors, VEGF is well known to have an important function in the pathogenesis of ALS. [31][32][33][34]37,38 The genetically modified human NSCs we established, F3.VEGF cells, were confirmed to release four times of VEGF165, the most abundant and biologically active isoform in vivo, compared with the parental F3 cells as we have reported previously in animal models of stroke. 28 Ex vivo gene therapy by genetically modified cells to carry growth factor gene has no risk related with virus injection during the in vivo gene therapy, and the transplanted cells can deliver growth factor over a large area as the cells migrate and are integrated to the host brain tissue.…”
Section: Discussionsupporting
confidence: 59%
“…37 In SOD mutant mice, a significant downregulation of VEGF mRNA expression in spinal cord was found early in the course of the disease indicating that dysregulation of VEGF posttranscriptional processing reduces VEGF levels. 31 Subsequent follow-up human genetic studies have shown that 'low-VEGF' haplotypes in the VEGF promoter had an increased risk of ALS in the European population. 38 Several reports have also reported low VEGF levels in the colony-stimulating factor of ALS patients, [32][33][34] and the expression of both VEGF and VEGFR2 was downregulated on the anterior horn motoneurons as compared with the normal controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions, which are specific to mutant SOD1, negatively affect levels of VEGF mRNA, which is a neuroprotective factor for motor neurons (Lu and others 2007;Lu and others 2009). Similarly, mutant SOD1 has been shown to bind the 3′ UTR of the neurofilament light chain (NFL) mRNA and negatively affect its stability.…”
Section: Sod1 As An Rna Binding Proteinmentioning
confidence: 98%
“…Whilst evidence of a role for SOD1 in the former two is still lacking, mutant SOD1 can bind mRNAs and play a role in their stabilization (Lu and others 2007;Lu and others 2009;Chen and others 2014). Wildtype SOD1 has further been shown to interact with TDP43, suggesting a potential common action in the regulation of specific RNA stability (Volkening and others 2009).…”
Section: Sod1 As An Rna Binding Proteinmentioning
confidence: 99%